Reaktualisasi Proses Penyidikan oleh Kepolisian Berbasis Nilai-Nilai Pancasila dan Optimalisasi Pemanfaatan Teknologi - Ira Alia Maerani (Unissula, 2015)
Indonesian Criminal Justice System consists of the police, public prosecutor and the courts. The role of the police investigators is certainly vital as the frontline in building public confidence in the rule of law in Indonesia. The role of the investigator is very big in the realization of justice in society. The era of globalization which demands a pattern of life that is fast-paced, instant, measurable, and transparent requires investigators to follow the times by optimizing the use of technology. The aim is to give effect to the rule of law in Indonesia that provides fairness, expediency and certainty. However that must be considered is the priority values of Pancasila in the process of inquiry and investigation. The values of supreme divinity, God (religious), humanity, unity, democracy and justice are values that establish a balance (harmony) in enforcing the law. Law and its implementation so that the product meets the demands for social justice. This paper will examine the role of the investigator according to positive law currently in force as well as the role of investigator in implementing the values of Pancasila, accompanied by optimizing the use of technology.Keywords: Re-actualizing, Investigation, Police, values of Pancasila, Technology